Insulin Resistance and C-reactive Protein in Preeclampsia - Milan Stefanović; Predrag Vukomanović; Mileva Milosavljević; Ranko Kutlešić; Jasmina Popović; Aleksandra Tubić-Pavlović (Biomolecules & Biomedicine, 2009)
Preeclampsia is referred to as the “disease of the theories” because of the multiple hypotheses proposed to explain is occurrence. Despite considerable research, the causes of preeclampsia remain unclear. Preeclampsia is likely to be multifactorial in origin, and recent research has focused on endothelial dysfunction as a central abnormality in preeclampsia. Insulin resistance and inflammation may contribute to the onset of preeclampsia. They could also be correlated. The aim of the study was to evaluate the presence and relationship between insulin resistance and its markers and C-reactive protein as a marker of inflammation. During their third trimester, 17 preeclamptic women and 20 normotensive controls underwent oral glucose tolerance test, basic biochemical analyses and SHBG. Preeclamptic women were more insulin resistant (p=0,004), and they had higher triglycerides levels (p=0,006), uric acid (p=0,002). However, the study groups did not differ in C-reactive protein (CRP), sex hormone-binding globulin (SHBG), high and low-density lipoproteins (HDL-cholesterol and LDL-cholesterol). In multiple regression analysis only SHBG (p=0,014) and triglycer-ides (p=0,003) were associated with insulin sensitivity independently of the body mass index (BMI), weight gain, HDL and LDL, and CRP. Preeclampsia is a state of increased insulin re- sistance, and CRP as the marker of inflammation was not increased in our research, and not associated with established preeclampsia.